A dimensão espacial e o proceder pedagógico - Nóbrega Júnior, Orgival Bezerra da (2014)
This research was conducted at the Post Graduate Program in Education at the Federal University of Rio Grande do Norte. It had the aim to understand the spatial conception associated with the pedagogical action. It promoted a historical-scientific approach to concepts of space to emphasize the spatiality from the geographical and educational theoretical referential. In it empiria situated in a university student universe, has utilized a quantitative measuring instrument as a subsidy to a qualitative dialogical analysis. It showed a synthetic framework arising from the interaction and the reflection focused into problems, challenges and potential of a pedagogical vision that considers the spatiality of teaching education. It seeks to promote delineations of paths pedagogical to a integrate approach of heterotopic space conception, as a necessary critical condition to the appropriation of social reality without doing the epistemological dichotomy, enhancing it signification to the learning academic teaching ambience; as well the scientific and teaching formation in the geography course